Psychological Stress in relation to self- confidence and some basic skills performance on the Floor- Exercises in the artistic gymnastics for women - Khalid, Zana; Adnan, Ban; Laiz, Kholoud (Journal of Physical Education, 2013)
there are deferent effects for psychological stress from a student to another according to the events and situations that pass by and exercises relieves stress and effect on reinforcement of self-confidence. The problem is that psychological stress affect the skills performance of the student and may be negative or positive and self-confidence is the key which helps students to make decision in hard and sudden positions. research aims measuring the level of psychological stress and self confidence and some skills performance on the table movements land in the artistic gymnastics ,and the purpose came on to confirm this statistical relationship , has been used descriptive method manner survey to fit the nature of research and the sample consisted of some students from the third grade in the college of Physical Education, University of Baghdad and of second number was (40) students, researchers concluded that psychological stress had an impact on the level of performance for second grade has students and they recommended that attention should be paid for psychological aspects for the students and enhance self-confidence because of the importance evident in level of skills performance in gymnastics